Regulating Pre-Marital Debts in Indonesian Marital Property Law - Nurhayati; Narsudin, Udin; N, F. Davy Gunadi (International Journal of Latin Notary, 2025)
This study explores the legal treatment of pre-marital debt in Indonesia’s marital property regime, particularly in the absence of prenuptial agreements, and assesses the regulatory implications for spousal autonomy and legal certainty. Although Indonesian law distinguishes between joint and separate property, it lacks clear provisions governing the classification and enforcement of financial obligations incurred prior to marriage. Drawing upon statutory analysis and landmark case law, the research reveals a significant normative gap in how pre-marital debts are addressed, often leaving spouses vulnerable to unpredictable liabilities and judicial discretion. Through a comparative legal approach, the study evaluates regulatory models from the Netherlands, the United States, and the United Kingdom—jurisdictions that apply rigorous safeguards such as mandatory financial disclosure, independent legal advice, and substantive fairness reviews in the enforcement of prenuptial agreements. These systems emphasize informed consent and contractual autonomy, while also protecting economically vulnerable spouses through equitable enforcement standards. The analysis highlights the need for Indonesia to reform its legal framework to ensure fairness and predictability in marital financial arrangements, particularly in light of increasing cross-border marriages and complex property dynamics. The study recommends the adoption of mandatory debt disclosure laws, procedural safeguards for marital contracts, and harmonization strategies aligned with international best practices in private family law.